The Role of Digital Media Against Zakat Fundraising in The Perspective of Sharia Economic Law (Research Study at the IZI Institute) - Wahyudi Wahyudi; Hidayat Hidayat; Hendra Kholid (CV. Publikasi Indonesia, 2024)
This study explores the use of digital media for zakat fundraising at IZI, explains its implementation within the framework of Sharia economic law, and its impact on increasing zakat collection. IZI's approach to digital media-based zakat fundraising is not only interesting but also educational and diverse. The purpose of this study is to investigate and analyze the strategy and effectiveness of using digital media in collecting zakat funds by zakat institutions, focusing on the Indonesian Zakat Initiative (IZI). Methodologically, the study used a variety of techniques, including interviews with relevant personnel at IZI, literature review within the institution, direct observation of zakat contributors to IZI, and qualitative analysis through graphical representation of zakat collections over time. This method is carried out meticulously in collaboration with IZI staff to ensure data accuracy. The result of this study is that the adoption of zakat fundraising through digital media at IZI has proven effective and diverse. Collaboration with Tokopedia through